Constructing a digital in-line holography (DIH) set-up and analyzing particles with different characteristics - Trivedi, Shamna Mukesh (Kansas State University, 2024)
Atmospheric aerosols play a significant role in our understanding of climate change, processes taking place in the atmosphere and certain biological transport systems. Imaging these aerosols and determining their distinct characteristics, like size and shape, is a challenge. We need a way to sample and resolve the size and shape of aerosols in real-time. One way this has been done successfully in the past is through Digital In-line Holography (DIH). A simple DIH set-up was constructed with stationary particles as samples. I first learned how to align the laser beam used in the set-up. Following that, I optimized the beam width by selecting appropriate lens and pinhole. I could then use the CCD sensor to get the images of the beam with or without particles present. Without particles present, the image formed was named “reference measurement” and the image formed with particles was named “raw measurement”. A contrast hologram is the reference measurement subtracted from the raw measurement. This contrast hologram can then be computationally processed to obtain an image of the particle. This was done using a Mathematica code which transforms the contrast hologram using Fresnel equations, solved using Fourier transforms, into an image of the particle. Different micro-spheres of known diameters (50μm, 40μm, 30μm, and 15μm) were imaged to gauge resolution of the set up. To verify the results, these particles were also imaged using an optical microscope. The resolution limit of the set-up is more than 15μm. Following this, I checked the accuracy of the setup by imaging samples containing a mix of various sizes and shapes and comparing them to digitally calibrated images of the same particles using the optical microscope. 10 such samples were analyzed out of which I have discussed Fe₂O₃, NaCl, and Road Dust. Thus, while the resolution of the set-up is less than the theoretical limit, accurate results can be obtained in certain ranges.
Keywords: Atmospheric aerosol; Optics; Digital holography; Laser